2022
DOI: 10.5812/ijpbs-113591
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depression, and Quality of Life in Caregivers of Children with Cleft Lip and Palate: A Systematic Review

Abstract: Context: Cleft Lip and Palate (CL/P) is the most common craniofacial malformation in the oral cavity, with a prevalence of “1 to 2in 1,000 live births worldwide. Parents with CL/P children are more prone to experience emotional disorders, especially depression, and have higher child-related stress than the parents of normal children. Due to the effect of the mental status of parents on children, the assessment of the psychological aspects of this problem and its effects on the patients and their parents is cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The challenges continue with frequent hospital visits, coping with the anxiety of the first anesthesia, witnessing their child's discomfort after surgery, and caring for their infant, especially in the first year of life. 26 In their systematic review, Namdar et al 27 reported that 6 of 19 studies evaluating anxiety in mothers with CL/P children demonstrated higher anxiety levels among mothers with CL/ P children than in the general population. Similar to the present study, another study conducted in the Turkish population reported that mothers of infants born with CL/P had higher mean parenting stress scores than the mothers of healthy infants, regardless of cleft type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges continue with frequent hospital visits, coping with the anxiety of the first anesthesia, witnessing their child's discomfort after surgery, and caring for their infant, especially in the first year of life. 26 In their systematic review, Namdar et al 27 reported that 6 of 19 studies evaluating anxiety in mothers with CL/P children demonstrated higher anxiety levels among mothers with CL/ P children than in the general population. Similar to the present study, another study conducted in the Turkish population reported that mothers of infants born with CL/P had higher mean parenting stress scores than the mothers of healthy infants, regardless of cleft type.…”
Section: Discussionmentioning
confidence: 99%
“…In their systematic review, Namdar et al 27 reported that 6 of 19 studies evaluating anxiety in mothers with CL/P children demonstrated higher anxiety levels among mothers with CL/P children than in the general population. Similar to the present study, another study conducted in the Turkish population reported that mothers of infants born with CL/P had higher mean parenting stress scores than the mothers of healthy infants, regardless of cleft type.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that mothers are in charge of performing the massage, it is essential to investigate their emotional state and mental health since, as reported by Namdar et al 15 they have a greater tendency to show depressive signs than mothers of children without CL/P, 16 which can be enhanced by the feeling of guilt reported by some mothers for not being able to carry out the indicated therapy. It would be appropriate to assess the mental health of the mothers of children with CL/P as a screening method for those who need support in this area, which would improve adherence to physical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There are internationally recognised psychosocial impacts on whānau, especially those with lower household incomes. [6][7][8] Psychosocial wellbeing and positive engagement with services has been strongly linked with early diagnosis and counselling, establishing a close relationship with the MDT and social supports. 7…”
Section: Auckland Regional Cleft Palate Service: Service Accessibilit...mentioning
confidence: 99%